Hb Hubei [α114(GH2)Pro→His, HBA1: c.344C>A]: A Novel Hemoglobin Variant of the α1-Globin Chain. (4th May 2018) - Xu, An-Ping; Li, Jie; Chen, Wei-Dong; Zhou, Yu; Ji, Ling
Abstract: We report here a novel α1-globin chain variant, Hb Hubei [α114(GH2)Pro→His, HBA1 : c.344C>A], in a Chinese individual. The proband, a 28-year-old Chinese female, was discovered following routine Hb A1c analysis using cation exchange high performance liquid chromatography (HPLC). Sanger sequencing revealed a novel missense mutation, HBA1 : c.344C>A (C C C>C A C), in exon 2 of the α1-globin gene. The mutation caused a transition of proline to histidine at position α114(GH2) on the α1-globin chain. This new variant was named Hb Hubei after the geographic origin of the proband.